158 Quantifying manganese-calcium interaction for optimal cardiac manganese enhanced mri. (5th June 2017) - Jasmin, Nur Hayati; Roberts, Thomas; Connell, John; Lythgoe, Mark; Stuckey, Daniel
Abstract : Introduction: Information on myocardial viability is important for the management of ischaemic cardiomyopathy patient. Difficulties in assessing viability arise because necrotic tissue and viable myocardium overlap at the infarct border zone. Manganese-enhanced MRI (MEMRI) is sensitive to viability and the inotropic state of the heart 1 . Mn 2+ enters viable cardiomyocytes via Ca 2+ channels and enhances intracellular T1 relaxation. As intracellular Ca 2+ is a central regulator of cardiac contractility high Mn 2+ concentration can be cardiotoxic. Here, Mn 2+ salt has been supplemented with Ca-gluconate to provide a Calcium supplement that should overcome inotropy while still providing enhancement of viable myocardium. Methods/Materials: Two manganese-based media were used: 50 mM MnCl2 in saline and 50 mM MnCl2 in a 1:3 ratio with 58 mM Ca-gluconate. MEMRI experiments were performed at baseline and 7, 14, 21, 28, 35, and 42 min after intraperitoneal injection of Mn (n=4) or Mn-CaG (n=3) into adult male C57B1/6 mice using a 9.4T MRI system. Using a look-locker inversion recovery sequence 2 a series of 12 short-axis gradient echo images were acquired with the following parameters: TE=0.99 ms, TRir = 3s, TI = 100–1300 ms, FOV=25.6mm 2, DM=128 2, FA=10Ã, Â°, slice thickness=1.5 mm. Cardiac function was assessed using cine-MRI. For T1 analysis, the average signal intensity in myocardium and blood pool regions were calculated using Segment, and were fitted to an exponential curve. Results: T1 values were evaluated at each time point and compared between two groups. Both manganese-based media rapidly led to significant shortening of T1 in the myocardium and the blood and these changes remained stable over the course of the experiment. The peak reduction of T1 in the myocardium and blood was observed slightly earlier for Mn than for Mn-CaG (figure 1a), although this difference did not reach significance in this pilot study. Image enhancement in cine-MRI was similar in the Mn-CaG group and the Mn group (figure 1b). Importantly no alterations in cardiac function or heart rate were observed and all mice recovered fully, indicating [Mn 2+ ] used was below cardiotoxic levels. Conclusion: The present study indicates that Ca 2+ supplements to Mn 2+ does not affect cardiac function while producing an optimum image quality. This approach has the potential of reducing the risk of toxicity of manganese-based agents and could be used to identify salvageable myocardium and monitoring new growth of heart tissue after stem cells therapy. References: . Hu TCC, et al. (2001). Magnetic Resonance in Medicine. Price AN, et al. (2011). Journal of Cardiovascular Magnetic Resonance.